Differentiated Learning Management in Class X Islamic Religious Education Lessons at Madrasah - Nursamsiah Br Ginting; Hasrian Rudi Setiawan; Indra Prasetia (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
This study attempts to characterize the use of differentiated learning management in Islamic religious education classes at MAN Karo in Kabanjahe, North Sumatra, specifically in class X. This study employs descriptive research methodologies in a qualitative manner. The information used by the author to describe the organization, implementation, supervision, and evaluation of differentiated learning comes from responses, opinions, and information that is described in the form of problems using data collection techniques such as interviews, documentation, and observation. The study's findings indicate that MAN Karo's implementation of differentiated learning management in Islamic religious education classes has been successful and efficient in four areas: first, class organization; second, learning resource organization; and third, learning methods or models. These strategies allow students to become well-conditioned before class, during class, after instruction, and during evaluation. Second, differentiation in learning environments, products, procedures, and content is part of implementation. Third, monitoring, supervision, assessment, reporting, and follow-up tasks are all included in regular and continuous supervision.